Vogais postônicas não-finais: do sistema ao uso - Silva, André Pedro da (2010)
This paper describes the behavior of variable medial post-stressed vowel in nouns, in the dialect of the town of Sapé, located in the state of Paraiba. In this context, there were done two analyses. The first one is a variationist, in order to verify the effects of deletion of the medial post-stressed vowel, and compare the results with other studies of similar nature. To do so, we adopted the theoretical basis in Labov (1972) and Weinreich; Labov; Herzog (1968). The second analysis, phonological character, focused on analyzing the processes triggered either by resistance to syncope - the raising and rounding of the medial post-stressed vowels, based on Câmara Jr. (2002 [1970]) and Battisti; Vieira (2005) the former one is an occurrence of syncope: assimilation, resyllabification and restructuring of the feet, from two theoretical models Metrical Phonology: The Selkirk (1982) on the syllable, and Hayes (1995) on the accent. Under the Sociolinguistics Variation point of view, one analyzed statistically, linguistic and social variables that favor the deletion of the medial post-stressed vowel. The results were compared to those of other studies that aimed to investigate the same phenomenon, but with speech data from other regions of Brazil. It was found that the fact of year of schooling is the most important one in the medial poststressed vowels deletion in three out of four works under study, as well as the following phonological context, which was considered the most conducive to the process focused on this study. But Amaral (1999) and Lima (2008) state that the liquid vibrant is the most vibrant favoring the process of deletion, while Silva (2006) and Ramos (2009), state that the liquid side is the one. Thus, after the erasure process it occurs medial post-stressed vowel, the consonantal segment remaining after the deletion is incorporated herein to the stressed syllable, either to attack the unstressed final syllable, through resyllabification, causing a restructuring of syllabic feet, transforming them into penultimate stressed words as, respectively: música ~ musca and xícara ~ xicra. whenever this deletion does not occur, the medial post-stressed vowels [e] and [o] face prosecution for opening, for example, in a.bó.b[o].ra ~ a.bó.b[o].ra, and revolt in ár.v[o].re ~ ár.v[o]re. It is through this process of assimilation that a segment assimilates characteristics of the previous segment, as in física ~ [fizga], and/or segment, as in música ~ [musca].